Uterine balloon tamponade as an adjunct to misoprostol for the treatment of uncontrolled postpartum haemorrhage: a randomised controlled trial in Benin and Mali. Issue 9 (1st September 2017) - Dumont, Alexandre; Bodin, Cécile; Hounkpatin, Benjamin; Popowski, Thomas; Traoré, Mamadou; Perrin, René; Rozenberg, Patrick
Abstract : Objective: To assess the effectiveness of low-cost uterine tamponade as an adjunct to misoprostol for the treatment of uncontrolled postpartum haemorrhage (PPH) in low-resource settings. Design: Randomised controlled trial. Setting: Seven healthcare facilities in Cotonou, Benin and Bamako, Mali. Population: Women delivering vaginally who had clinically diagnosed PPH that was suspected to be due to uterine atony, who were unresponsive to oxytocin and who needed additional uterotonics. Methods: Women were randomly assigned to receive uterine balloon tamponade with a condom-catheter device or no tamponade; both groups were also given intrarectal or sublingual misoprostol. Main outcome measure: Proportion of women with invasive surgery or who died before hospital discharge. Results: The proportion of primary composite outcome did not differ significantly between the tamponade arm (16%; 9/57) and the standard second line treatment arm (7%; 4/59): relative risk 2.33 (95% CI 0.76 to 7.14, p=0.238). A significantly increased proportion of women with tamponade and misoprostol versus misoprostol alone had total blood loss more than 1000 mL: relative risk 1.52 (95% CI 1.15 to 2.00, p=0.01). Case fatality rate was higher in the tamponade group (10%; 6/57) than in the control group (2%; 1/59) (p=0.059). Trial registration number: ISRCT Registry Number 01202389; Post-results.